Transregional and Regional Elites - Connecting the Early Islamic Empire. - Hagemann, Hannah-Lena.; Heidemann, Stefan (Berlin/Boston : Walter de Gruyter GmbH, 2020)
Studies in the History and Culture of the Middle East are published as supplement to Der Islam which was founded in 1910 by Carl Heinrich Becker, an early practitioner of the modern study of Islam. The mission of the series is the study of past societies of the Middle East, their belief systems, and their underlying social and economic relations--in their aim to cover the entire spectrum of the historically oriented humanities and social sciences.
Intro -- Table of Contents -- Introduction: Transregional and Regional Elites - Connecting the Early Islamic Empire -- Studying Elites in Early Islamic History: Concepts and Terminology -- Arabia and Iraq -- Insult the Caliph, Marry al-Ḥasan, and Redeem Your Kingdom: Freiheitsgrade of Kindī Elites During the 7&lt -- sup&gt -- th&lt -- /sup&gt -- to 9&lt -- sup&gt -- th&lt -- /sup&gt -- Century -- Landowners in Lower Iraq during the 8&lt -- sup&gt -- th&lt -- /sup&gt -- Century: Types and Interplays -- The Rise and Fall of the Early ʿAbbāsid Political and Military Elite -- The East -- Who Were the Mulūk Fārs? -- An Empire of Elites: Mobility in the Early Islamic Empire -- Preliminary Notes on the Term and Institution of al-Shākiriyya in Early Islam (ca. 14-218 H/635-36-833 CE) Mainly According to the Arabic Sources -- The Eastern Mediterranean and the North -- Khurāsānī and Transoxanian Ostikans of Early ʿAbbāsid Armenia -- The Governors of al-Shām and Fārs in the Early Islamic Empire - A Comparative Regional Perspective -- Muslim Elites in the Early Islamic Jazīra: The Qāḍīs of Ḥarrān, al-Raqqa, and al-Mawṣil -- Christian Elite Networks in the Jazīra, c.730-850 -- The West -- Establishing Local Elite Authority in Egypt Through Arbitration and Mediation -- The Civilian Ruling Elite of the Ṭūlūnid-Ikhshīdid Period -- Connecting the Ibāḍī Network in North Africa with the Empire (2&lt -- sup&gt -- nd&lt -- /sup&gt -- -3&lt -- sup&gt -- rd&lt -- /sup&gt -- /8&lt -- sup&gt -- th&lt -- /sup&gt -- -9&lt -- sup&gt -- th&lt -- /sup&gt -- Centuries) -- Indices -- Index of names -- Index of places -- Index of subjects.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books